Linear electrostatic waves in twotemperature electron–positron plasmas - Lazarus, I.J.; Bharuthram, R.; Singh, S.V.; Pillay, S.R.; Lakhina, G.S. (My University, 2012)
Linear electrostatic waves in a magnetized four-component, two- temperature electron–positron plasma are investigated, with the hot species having the Boltzmann density distribution and the dynamics of cooler species governed by fluid equations with finite temperatures. A linear dispersion relation for electrostatic waves is derived for the model and analyzed for different wave modes. Analysis of the dispersion relation for perpendicular wave propagation yields a cyclotron mode with contributions from both cooler and hot species, which in the absence of hot species goes over to the upper hybrid mode of cooler species. For parallel propagation, both electron-acoustic and electron plasma modes are obtained, whereas for a single-temperature electron–positron plasma, only electron plasma mode can exist. Dispersion characteristics of these modes at different propagation angles are studied numerically.
Keywords: Linear electrostatic waves; Temperature electron–positron plasma; Boltzmann distribution law; Cyclotron waves; Plasma waves; Electromagnetic waves